Impact of Coronavirus Disease 2019 Pandemic on Providing the Objective Structured Clinical Examination: A Faculty of Pharmacy Guidance - Reem M. Diri; Hussain T. Bakhsh (Journal of King Abdulaziz University: Medical Sciences, 2021)
The outbreak of the Coronavirus disease 2019 pandemic presented a challenge for every Faculty of pharmacy that conduct objective structured clinical examinations throughout the academic year. It is necessary to ensure that pharmacy students are well-trained and prepared to enter the clinical workforce during the crisis caused by this pandemic. Due to the pandemic, the Faculty of Pharmacy at King Abdulaziz University embraces the challenge of ensuring that the upcoming pharmacy students will complete their academic year requirements, including the objective structured clinical examination. This paper provides details of how the objective structured clinical examination was designed and managed during the coexisting Coronavirus disease 2019 pandemic. It also assists other faculties of pharmacy that need to plan objective structured clinical examinations to ensure the validity and reliability of performance assessments while protecting the safety of all participants.